The role of asteroid strength, porosity and internal friction in impact momentum transfer - Raducan,SD; Davison,TM; Luther,R; Collins,GS (Icarus, 2019)
Earth is continually impacted by very small asteroids and debris, and a larger object, though uncommon, could produce a severe natural hazard. During impact crater formation the ballistic ejection of material out of the crater is a major process, which holds significance for an impact study into the deflection of asteroids. In this study we numerically simulate impacts into low-gravity, strength dominated asteroid surfaces using the iSALE shock physics code, and consider the Double Asteroid Redirection Test (DART) mission as a case study. We find that target cohesion, initial porosity, and internal friction coefficient greatly influence ejecta mass/velocity/launch-position distributions and hence the amount by which an asteroid can be deflected. Our results show that as the cohesion is decreased the ratio of ejected momentum to impactor momentum, β−1, increases; β−1 also increases as the initial porosity and internal friction coefficient of the asteroid surface decrease. Using nominal impactor parameters and reasonable estimates for the material properties of the Didymos binary asteroid, the DART target, our simulations show that the ejecta produced from the impact can enhance the deflection by a factor of 2 to 4. We use numerical impact simulations that replicate conditions in several laboratory experiments to demonstrate that our approach to quantify ejecta properties is consistent with impact experiments in analogous materials. Finally, we investigate the self-consistency between the crater size and ejection speed scaling relationships previously derived from the point-source approximation for impacts into the same target material.